ENGAGING MATHEMATICS LEARNING STRATEGIES FOR ELEMENTARY SCHOOL STUDENTS - Devi Melani (CV. Fahr Publishing, 2024)
This study aims to investigate effective and enjoyable mathematics learning strategies for elementary school students, focusing on how such approaches can enhance both conceptual understanding and affective engagement. Utilizing a library research method, the study systematically reviews and synthesizes relevant literature from the past five years, drawing from peer-reviewed journal articles, books, and academic reports. The results identify six key strategies—game-based learning, use of manipulatives, storytelling, collaborative group tasks, digital simulations, and mathematics contextualized through local culture—as having significant cognitive and emotional impacts. Among these, game-based and contextual strategies demonstrated the highest gains in student engagement and achievement. The novelty of this research lies in its comprehensive integration of multiple strategy types within a socio-cultural and pedagogical framework, while also emphasizing the role of teacher implementation fidelity in successful strategy adoption. Unlike previous studies that often focus on single interventions or short-term outcomes, this study proposes a holistic, student-centered, and contextually responsive instructional approach. The findings support the assertion that enjoyable learning is not a pedagogical luxury, but a necessity for fostering mathematical literacy and motivation in young learners. In conclusion, the study provides strong theoretical and practical justification for embedding fun-based, culturally relevant, and multi-modal strategies in elementary mathematics classrooms, while also offering a conceptual foundation for future empirical research and curriculum development.